2021
DOI: 10.1021/acs.jpcc.1c01551
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Structural and Energetic Properties of Ammonium Perchlorate at Interfaces

Abstract: We investigated the structural and energetic properties of the ammonium perchlorate (AP) crystal in bulk and at interfaces using molecular dynamics (MD) simulations and density functional theory (DFT) calculations. Thermal rotations of ammonium ions were observed in the bulk AP crystal at room temperature, in agreement with experimental findings. We investigated atomic density distributions near six crystallographic surfaces of the AP crystal. We observed significant thermal rotations of perchlorate ions near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…The empirical potential approach (e.g., ReaxFF , ) has been widely used in investigating the initial decomposition pathways of energetic materials induced by thermal and mechanical stimulation. Recently, MD simulations have been performed to reveal the atomic insights behind the mechanical and structural properties of AP. Yeh and Andzelm investigated the structural and energetic properties of the ammonium perchlorate (AP) crystal in bulk and at interfaces using molecular dynamics (MD) simulations. They observed significant changes in the atomic density distributions of the AP crystal and near surfaces compared to the corresponding distributions in the bulk phase.…”
Section: Introductionmentioning
confidence: 99%
“…The empirical potential approach (e.g., ReaxFF , ) has been widely used in investigating the initial decomposition pathways of energetic materials induced by thermal and mechanical stimulation. Recently, MD simulations have been performed to reveal the atomic insights behind the mechanical and structural properties of AP. Yeh and Andzelm investigated the structural and energetic properties of the ammonium perchlorate (AP) crystal in bulk and at interfaces using molecular dynamics (MD) simulations. They observed significant changes in the atomic density distributions of the AP crystal and near surfaces compared to the corresponding distributions in the bulk phase.…”
Section: Introductionmentioning
confidence: 99%
“…AP slabs used in QM calculations by Yeh and Andzelm 13 contain at least seven distinct layers of ammonium or perchlorate ions, which is significantly smaller than those used in MD simulations in this study. Three different types of simulation protocols were applied to see the effect of limited system sizes in QM calculations: (1) Atomic positions in two middle layers of the AP slab and lateral dimensions parallel to the interfaces were fixed at the bulk values while the positions in other layers were allowed to be optimized.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…In this work, the (210), ( 001), ( 010), (100), (101), and (011) surfaces of AP were simulated using different force field parameter sets optimized to reproduce the lattice parameters of the bulk AP crystal to determine which agreed best with the corresponding surface energies estimated from QM calculations. 13 Using the best performing force field parameter set, simulations of the HTPB polymer binder in contact with the AP surfaces were performed. Strong interactions between the HTPB hydroxyl groups and the AP surface were observed to occur and could potentially corroborate previous suggestions that the interaction of the hydroxyl groups at the AP interface might explain differences in the AP−HTPB interfacial tension that are dependent on the AP surface.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the AR-XPS analysis, we can know that the surface of ADN-1% MMT is covered with more −NO 2 groups. It can be concluded that −NO 2 groups have lower surface energy than NH 4 + ions, so the ADN-1% MMT shows lower surface energy characteristics and narrower surface energy distributions (see PDI values in Figure d). The lower the surface energy, the better the flowability .…”
Section: Resultsmentioning
confidence: 99%